Ekokritik: Kritik Sastra Berwawasan Lingkungan - Siswo Harsono (KAJIAN SASTRA, 2008)
Literary criricism has recently undergone diverse growth. One school of literary criticism appealing most in America nowadays is ecocriticism. Theoretically, ecocriticism grew out of awareness of the interdependence of literature on environment. Environmental matters have profoundly been discussed over disciplines; ecology, technology, economics, philosophy, psychology, sociology, anthropology, Iaw and others. Environmental study centers, environmentol NGOs and environmental movements hove frequently emerged. These symptoms have been a challenge for literary scholarships to participate. Yet the foremost question is what role the literary scholarships can take to answer the question on the environmental matters. And the role is what ecocriticism about to point.